Pengaruh Green Accounting, Corporate Social Responsibility dan Good Corporate Governance Terhadap Profitabilitas Perusahaan Manufaktur Yang Terdaftar di BEI (Tahun 2018-2021) - Purbawati, Husna Nadea Ulhaq; Mujiyati, Mujiyati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to empirically examine the effect of green accounting, corporate social responsibility and good corporate governance proxied by managerial ownership, institutional ownership, and audit committee on profitability proxied by the company's ROA (Return On Assets). The population in this study is manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample of this study was determined by purposive sampling method so that as many as 10 companies met the research criteria with a total of 38 samples. The analysis method used is multiple linear regression analysis. The results provide evidence that green accounting, corporate social responsibility, managerial ownership, and audit committees have no effect on profitability. While institutional ownership affects profitability